2018
DOI: 10.24114/lt.v14i2.8368
|View full text |Cite
|
Sign up to set email alerts
|

Language Use Between Male and Female Host in Hitam Putih Talk Show

Abstract: This study discusses about language use occurred by male and female host in Hitam Putih talk show. The method of this research is descriptive qualitative. The subjects of this study are male and female host in Hitam Putih talk show. The data are the utterances produced by male and female host in Hitam Putih talk show. This research focuses on the show broadcasted on October 2016 by taking 4 videos randomly. The objective of this study is to describe kinds of the language use uttered by male and female host in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Subsequently, this study is opposed to Xia's (2013) theory and also the reviewed related research by Sari (2017) which stated that men tend to use more swear words than women. This is because in this study found that lead female character are swearing much more than lead male character.…”
Section: Swear Words and Expletivesmentioning
confidence: 83%
See 1 more Smart Citation
“…Subsequently, this study is opposed to Xia's (2013) theory and also the reviewed related research by Sari (2017) which stated that men tend to use more swear words than women. This is because in this study found that lead female character are swearing much more than lead male character.…”
Section: Swear Words and Expletivesmentioning
confidence: 83%
“…A Star Is Born (2018) is an American movie which was released in 05 October 2018. It is the third remake of the original 1937 film with the same title, after the 1954 and 1976.In particular, the main characters in this movie, Ally and Jack, are taken as the object of the analysis.A number of studies related to the differences of language use by both males and females were previously conducted by some researchers such as Ishikawa (2015), Sardabi and Afghari (2015), Dewi (2016), Dina and Ariyanti (2017), Sari (2017), and Wahyuningsih (2018). From those earlier studies, none of them utilized movie as their object of analysis.…”
Section: Introductionmentioning
confidence: 99%